A statistical assessment of the biological relationship between simultaneous canine mammary tumours. (10th October 2015) - Gunnes, G.; Borge, K. S.; Lingaas, F.
Abstract: Simultaneous canine mammary tumours (CMTs) are frequently reported in the literature, but few studies have addressed their biological relationship in detail or performed statistical assessments. In this study, 269 canine mammary gland tumours from 216 dogs were categorized using an extended histopathological classification, where semiquantitative and binomial scales enumerated morphological parameters of the tumours. The classification facilitated a statistical study of the biological relationship between simultaneous within‐dog tumours. Seventy‐seven percent of the dogs had single tumours and 23% had simultaneous tumours. Sixty‐one percent of the neoplasias were benign, with complex adenoma as the most frequent diagnosis and 39% were malignant, with complex carcinoma as the most common malignancy. Simultaneous tumours within dogs more often had equal diagnoses and neoplastic level (benign or malignant) than would be expected by chance alone, as compared with random pairs of single tumours from different dogs. This statistically supported finding indicated the presence of a biological relationship between simultaneous tumours.